PENGARUH LAYANAN KONSELING DENGAN TEKNIK BEHAVIOR CONTRACT DALAM MENGURANGI PERILAKU MENYONTEK SISWA DI SMA “X” DI SIDOARJO - Intan Kusuma Noviasari; Ghozali Rusyid Affandi; Eko Hardi Ansyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Cheating behavior is a deviant maladaptive behavior and has a negative impact, thus reflecting an interest in learning and learning that is not effective. The problem at SMA "X" in Sidoarjo is cheating behavior that occurs in students which is difficult to stop and becomes a culture every year. This study aims to determine the effect before and after counseling services are carried out with the behavior contract technique. This research method uses a pure experiment, namely Randomized Control Trial (RCT) in a random way to determine the experimental group and the control group in one class. The sample used was class 10 with a total of 20 students, 10 students became the experimental group and 10 students became the control group, each of which was given a pre-test and post-test using a Likert scale of cheating behavior. Data analysis technique used independent sample t test and paired sample test using JASP 0.16. Student cheating behavior before being given counseling services was 94.4 then after being given counseling it decreased by 76.3 and was supported by the hypothesis Ha was accepted because t = 3.606 p = 0.002 <0.05 and H0 was rejected, indicating a significant influence on the counseling behavior contract in reducing cheating behavior on students of SMA "X" in Sidoarjo.